Combining bio- and organocatalysis for the synthesis of piperidine alkaloids. Issue 11 (13th January 2022) - Taday, Freya; Cairns, Ryan; O'Connell, Adam; O'Reilly, Elaine
Abstract : A hybrid bio-organocatalytic cascade was developed for the preparation of piperidine alkaloids. Abstract : There is continued interest in developing cascade processes for the synthesis of key chiral building blocks and bioactive natural products (or analogues). Here, we report a hybrid bio–organocatalytic cascade for the synthesis of a small panel of 2-substituted piperidines, relying on a transaminase to generate a key reactive intermediate for the complexity building Mannich reaction.